Homecoming - Voigt, Cynthia (New York : Atheneum Books for Young Readers, 1981)
Abandoned by their mother, four children begin a search for a home and an identity.
Sequel: Dicey's song.
Elem. School Library Collection.
Wilson's Children.
Wilson's Junior High School.
6.3
6.3
Keywords: Family life -- Fiction; Survival -- Fiction; Family life -- Fiction; Survival skills -- Fiction